KEARIFAN LOKAL MASYARAKAT KABUPATEN MADIUN DALAM MENYIKAPI PANDEMI COVID-19 - Muhammad Hanif (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
Covid-19 pandemic has caused massive and widespread fear from various walks of life. The Covid-19 outbreak has affected all aspects of human life. This social reality encourages the people of Madiun Regency to make an effort to respond the pandemic by relying on local wisdom. The purpose of the study is to analyze and explain the actions of the people of Madiun Regency in responding to the Covid-19 Pandemic. The study was conducted for a year using a qualitative ethnographic approach. Data were collected by doing interview, observation, and document recording. The informants were determined by the purposive sampling technique. Meanwhile, the data analysis was using coding techniques. The results show that the community carries out mitigation through various activities vertically (supernatural powers) and horizontally (fellow humans and nature) in accordance with the philosophy of life of personal memayu hayuning, memayu hayuning kulawarga, memayu hayuning together, memayu hayuning bawana, including; (1) doing religious rituals, (2) carrying out ‘peduli tangga teparo’ (a caring-neighbor movement), (3) encouraging mutual cooperation in various aspects of life fulfillment with the principles of togetherness, mutual honing, compassion, and upbringing, (4) activating and mobilizing food barns and barns food storage, and growing medicinal plants and consuming them to increase immunity.